High-throughput additive manufacturing and characterization of refractory high entropy alloys. (June 2020) - Melia, Michael A.; Whetten, Shaun R.; Puckett, Raymond; Jones, Morgan; Heiden, Michael J.; Argibay, Nicolas; Kustas, Andrew B.
Graphical abstract: Highlights: Rapid screening of HEAs/CCAs was demonstrated via additive manufacturing and high-throughput mechanical testing. A comprehensive analysis was conducted on an exemplar BCC RHEA/CCA system of interest for harsh operating environments. The hardness of the additively manufactured samples significantly increased with increasing configurational entropy. Strain rate sensitivity of the alloys aligned with the expectations for conventional BCC metals and alloys. Implications suggest that the high-throughput approach could be implemented to accelerate HEA/CCA discovery. Abstract: Refractory High Entropy Alloys (RHEAs) and Refractory Complex Concentrated Alloys (RCCAs) are high-temperature structural alloys ideally suited for use in harsh environments. While these alloys have shown promising structural properties at high temperatures that exceed the practical limits of conventional alloys, such as Ni-based superalloys, exploration of the complex phase-space of these materials remains a significant challenge. We report on a high-throughput alloy processing and characterization methodology, leveraging laser-based metal additive manufacturing (AM) and mechanical testing techniques, to enable rapid exploration of RHEAs/RCCAs. We utilized in situ alloying and compositional grading, unique to AM processing, to rapidly-produce RHEAs/RCCAs using readily available and inexpensive commercial elemental powders. We demonstrate this approach with the MoNbTaW alloy system, as a model material known for having exceptionally high strength at elevated temperature when processed using conventional methods (e.g., casting). Microstructure analysis, chemical composition, and strain rate dependent hardness of AM-processed material are presented and discussed in the context of understanding the structure-properties relationships of RHEAs/RCCAs.